The impact of neuromarketing and influencer marketing on the decision process of generation Z consumers on the purchase of halal cosmetics - Ishomi, Asri Rahmah; Fatimah, Siska Ernawati; Curatman, Aang (Edelweiss Applied Science and Technology, 2025)
This study aims to help business actors understand Generation Z’s purchase decision. In addition, it examines the behaviour of Generation Z mediated by neuromarketing and influencer marketing in the decision to purchase halal cosmetics so that business actors can determine strategies by optimising product information and advertising. The population of this study is residents of Cirebon City aged 19 to 24 years, with a population of 56,626. The sampling used the Slovin formula and obtained as many as 397 respondents. To test the hypothesis of this study, samples were taken randomly using SEM-PLS (Partial Least Squares—Modeling Structural Equation) analysis. The study results show that neuromarketing and influencer marketing influence the purchase decision of Generation Z halal cosmetics through consumer behaviour. The dominating influence is influencer marketing in the decision to purchase halal cosmetics through the behaviour of Generation Z. Thus, the results of this research can be used by halal cosmetics business actors in Cirebon City to implement their business strategies using influencer marketing so that business continuity is also expected to be maintained.